Outdoor recreation and the private forest owner: Place attachment, social values, and public access - Johnsson, Frida; Beery, Thomas (Frontiers in Conservation Science, 2023)
Introduction The Swedish National Forest Program emphasizes that the forest can be more multifunctional where the values created by human experiences of the forest, i.e., social values, can be used for tourism and outdoor recreation, leading to rural development and sustainable growth. To develop multifunctional forests in this respect, private forest owners' perspectives on development are critically important. For example, the place attachment of the private forest owners affects how they manage their forests. Therefore, it is crucial to consider private forest owners' perspectives when planning land use. Method The study area is a region in southwest Sweden (Hallandsås) designated as a national interest area for outdoor recreation. There is interest in expanding and developing nature-based tourism, including trail systems, based on the perception of the areas as having great outdoor recreation value. This article aims to present findings from a study that investigated the potential for outdoor recreation development in the forests of Hallandsås. A questionnaire was sent out to private forest owners, which contained questions about social values, perspectives on the Swedish right of public access, development of outdoor recreation, and place attachment. Results The results showed that private forest owners considered health, well-being, and a good living environment the most important social values of their forested lands. The identity and cultural heritage value of private forest lands and the value of working on the land were the second and third most highly identified forest social values. Outdoor recreation was not identified as a top forest social value. Discussion The analysis identified seven key factors that must be considered with outdoor recreation development, given concerns and the importance of other forest social values. Careful consideration of these factors and their interactions can provide a path for outdoor recreation development that is respectful to people and places. This consideration is at the core of landscape protection and management as interpreted by the European Landscape Convention. Forest owners' social values are a critical part of landscape quality objectives, along with planning that links public aspirations with landscape character.